Mga hulwarang modyul sa pagtuturo ng Pilipino sa ikalawang grado para sa kaligirang unang wika - Mendoza, Elena A. 1943- (1978)
This study aimed to prepare individualized instructional materials in Pilipino for Grade Two pupils in the first language situation. The integrated approach was used to develop some specific skills in reading, vocabulary, structure and writing in modular form. This was tried out to sixty eight Grade Two pupils of the UPIS, representing three ability levels, fast, average and slow learners. The results pointed out that these materials are effective in teaching pupils of different ability levels, and that multidisciplinary approach and integration can be used effectively in presenting lessons in Communication Arts in Pilipino.
Appendices: leaves 160-182.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Filipino language -- Study and teaching (Primary).; Filipino language -- Programmed instruction; Teaching -- Aids and devices